Spherical bentonite pet sand and preparation method thereof
By mixing soap ore with modifier and granulation and drying, spherical soap ore for pet sand has been solved, and pet sand with low water absorption and prone to mildew are achieved.
Patent Information
- Application Number
- CN202411669721.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-11
AI Technical Summary
Existing cat litter products have problems such as high dust content, easy powdering, low water absorption, unstable agglomeration or the product is prone to mildew, high cost, and limited raw material sources.
The spherical soap ore is mixed with a modifier and grinded, then mixed with a granulation auxiliary agent to granulate, and finally dried to produce spherical soapy soapy pet sand. Modifiers include oleic acid amide, polyethylene glycol or sodium dodecylbenzenesulfonate.
The obtained spherical soapy soil pet sand has high water absorption, good clumping properties, low dust, never mold, environmentally friendly and clean. It hardly produces inhalable particles during use, has stronger weather resistance and low heavy metal content.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of pet product development, and in particular to spherical bentonite pet litter and a preparation method thereof. Background Art
[0002] Cat litter is an object used by cats to bury feces and urine. It has good water absorption and is usually used together with a cat litter box (or cat toilet). Pour an appropriate amount of cat litter into the litter box. When a trained cat needs to defecate, it will go into the litter box and deposit cat feces on it. The most important progress in cat culture is the use of cat litter. In the early days, cat litter was mainly non-condensing cat litter, and people mainly used it to collect cat feces. However, with the continuous advancement of cat litter technology, people are not limited to such a simple collection, so condensed litter, wood litter, crystal litter, bentonite litter, etc. have appeared continuously, with multiple functions and different advantages.
[0003] Chinese patent CN107897009A discloses a bentonite cat litter and a preparation method thereof. The components and weight ratios of the bentonite cat litter are as follows: 70-80 parts of bentonite powder, 35-45 parts of tourmaline powder, 35-45 parts of nano-TiO2 powder, 30-45 parts of hydroxyapatite powder, 20-25 parts of bamboo charcoal powder, 10-15 parts of camphor leaves, 10-15 parts of monsoon flowers, 15-20 parts of osmanthus fragrans, 10-15 parts of perennial perennial grass, 8-12 parts of celastrus, 15-18 parts of polypore, 20-25 parts of water, and 2-3 parts of edible pigment. The bentonite cat litter has strong water absorption effect, good deodorizing and sterilizing effect, is natural and pollution-free, can be buried as organic fertilizer, and has high utilization rate.
[0004] However, cat litter products in the prior art have problems such as high dust content, easy pulverization, low water absorption, unstable agglomeration or easy mildew, high cost, and limited raw material sources. Summary of the invention
[0005] The object of the present invention is to provide a spherical bentonite pet litter and a preparation method thereof. The spherical bentonite pet litter provided by the present invention has high water absorption rate, good agglomeration property, low dust, never mildews, and is environmentally friendly and clean.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing spherical bentonite pet litter, comprising the following steps:
[0008] The bentonite ore is mixed with a modifier and ground to obtain modified bentonite;
[0009] The modified bentonite and the granulation auxiliary agent are mixed and granulated to obtain wet pet litter particles;
[0010] Drying the wet pet litter particles to obtain spherical bentonite pet litter;
[0011] The modifier is one or more of oleamide, polyethylene glycol or sodium dodecylbenzene sulfonate.
[0012] Preferably, the weight ratio of the bentonite ore to the modifier is 100:0.5-5.
[0013] Preferably, the grinding is dry grinding.
[0014] Preferably, the mineral composition of the modified bentonite includes the following minerals in parts by weight: 90-100 parts of saponite, 1-5 parts of montmorillonite and 1-5 parts of quartz.
[0015] Preferably, the chemical composition of the modified bentonite includes the following components: SiO2 52-54%, Al2O3 15-17%, TiO2 0.2-0.5%, iron oxide 3-6%, MgO 4-6%, CaO 2-5%, K2O 0.05-0.15%.
[0016] Preferably, the loss on ignition of the modified bentonite is 10-20%.
[0017] Preferably, the granulation auxiliary agent is one or more of a water glass solution, a polyvinyl alcohol aqueous solution or an acrylamide aqueous solution.
[0018] Preferably, the volume percentage concentration of the polyvinyl alcohol aqueous solution is 5 to 10%;
[0019] And / or, the volume percentage concentration of the water glass solution is 5-10%;
[0020] And / or, the volume percentage concentration of the acrylamide aqueous solution is 5-10%.
[0021] Preferably, the drying temperature is 200-300°C;
[0022] The drying time is 10 to 30 minutes;
[0023] And / or, the particle size of the spherical bentonite pet litter is 1 to 4 mm.
[0024] The present invention also provides spherical bentonite pet litter prepared by the preparation method.
[0025] Beneficial effects of the present invention:
[0026] The present invention prepares spherical bentonite pet litter by using specific modified bentonite, so that the prepared spherical bentonite pet litter has excellent water absorption rate, agglomeration strength and deodorization effect, and has lower dust volume, stronger adsorption capacity, and almost no inhalable particles are generated during use. The product provided by the present invention will not mildew, produce toxins, or produce unfriendly odors during processing, storage, transportation and use, has stronger weather resistance, and has very low content of heavy metals such as lead and arsenic, has little impact on pet health, and is environmentally friendly. DETAILED DESCRIPTION
[0027] The present invention provides a method for preparing spherical bentonite pet litter, comprising the following steps:
[0028] The bentonite ore is mixed with a modifier and ground to obtain modified bentonite;
[0029] The modified bentonite and the granulation auxiliary agent are mixed and granulated to obtain wet pet litter particles;
[0030] Drying the wet pet litter particles to obtain spherical bentonite pet litter;
[0031] The modifier is one or more of oleamide, polyethylene glycol or sodium dodecylbenzene sulfonate.
[0032] In the present invention, the bentonite ore preferably uses saponite as the main functional component, and its trioctahedron is mainly composed of divalent magnesium ions, and the cations in the interlayer domain are mostly divalent cations, and the water adsorption capacity is in a more optimal state, which can achieve the maximum water absorption rate, and can improve the water absorption rate of cat litter and improve its agglomeration performance. The modified bentonite obtained by the preparation method of the present invention can effectively neutralize the excess surface unsaturated charge of clay minerals, thereby reducing the dust content of the product and improving its anti-powdering performance.
[0033] In the present invention, preferably, the weight ratio of the bentonite ore to the modifier is 100:0.5-5; preferably, the grinding is dry grinding; preferably, the mineral composition of the modified bentonite includes the following minerals in parts by weight: 90-100 parts of saponite, 1-5 parts of montmorillonite and 1-5 parts of quartz, wherein the montmorillonite is a general term for sodium montmorillonite and calcium montmorillonite without distinguishing between them; the quartz is α-quartz in mineralogy; preferably, the chemical composition of the modified bentonite includes the following components: SiO2 52-54%, Al2O3 15-17%, TiO2 0.2-0.5%, iron oxide 3-6%, MgO 4-6%, CaO 2~5%, K2O0.05~0.15%, the iron oxide described in the present invention is the sum of FeO and Fe2O3 without distinguishing the iron valence state; the chemical composition described in the present invention refers to the chemical composition determined by the silicate rock chemical analysis method (GB / T14506.1-14506.28-93), and can also be determined by other methods well known in the silicate field; "mineral composition" refers to the determination of mineral content using the X-ray powder diffraction internal standard method, and can also be determined by other methods well known in the relevant field. Preferably, the fineness of bentonite powder -200 mesh accounts for 88% to 94%. The "fineness -200 mesh" refers to powder that can pass through a 200 mesh sieve when sieved with a 200 mesh standard sieve.
[0034] In the present invention, preferably, the loss on ignition of the modified bentonite is 10-20%, and the loss on ignition refers to the mass reduction when the sample is burned to constant weight at 1000°C. The substances lost on ignition include but are not limited to adsorbed water, structural water, CO2 and SO2.
[0035] In the present invention, the granulation auxiliary agent is preferably one or more of water glass solution, polyvinyl alcohol aqueous solution or acrylamide aqueous solution; preferably, the volume percentage concentration of the polyvinyl alcohol aqueous solution is 5-10%; the volume percentage concentration of the water glass solution is 5-10%; the volume percentage concentration of the acrylamide aqueous solution is 5-10%.
[0036] In the present invention, the drying temperature is preferably 200-300° C.; the drying time is 10-30 min; and the particle size of the spherical bentonite pet litter is 1-4 mm.
[0037] The present invention also provides spherical bentonite pet litter prepared by the preparation method.
[0038] In actual production, the performance system and application indexes of the spherical bentonite pet litter described in the present invention can be tested according to the method specified in "Bentonite Cat Litter" (T / CAQI 377-2024).
[0039] The spherical bentonite pet litter of the present invention is suitable for the breeding of any urinating pet, and the pet is preferably a pet cat.
[0040] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0041] Example 1
[0042] A. Weigh 100 kg of natural bentonite ore at random from a large amount of natural bentonite ore, and then weigh 1.2 kg of oleic acid amide, mix the two evenly, and then dry grind them in a roller mill to obtain modified bentonite powder.
[0043] B. The chemical composition of the modified bentonite powder obtained was determined by the silicate rock chemical analysis method (GB / T14506.1-14506.28-93). As a result, the chemical composition of the modified bentonite powder obtained was: SiO2 53.39%, Al2O3 16.67%, TiO2 0.39%, iron oxide 5.28%, MgO 5.08%, CaO 3.38%, K2O 0.09%, and loss on ignition 15.33%.
[0044] The mineral composition of the obtained modified bentonite powder was determined by X-ray powder diffraction internal standard method. As a result, the mineral composition of the obtained modified bentonite powder was: saponite 92%, montmorillonite 4.6%, and quartz 3.4%.
[0045] C. The fineness of the modified bentonite powder obtained by sieving through a standard sieve. As a result, the fineness of the obtained modified bentonite powder was -200 mesh accounting for 93%.
[0046] D. The modified bentonite powder was granulated on a granulation disk with an aqueous solution containing 7% polyvinyl alcohol, and sieved to obtain wet spherical bentonite particles of 1-4 mm.
[0047] E. The wet spherical bentonite particles were dried at 260° C. for 20 minutes, and fine particles with a particle size of less than 1 mm were removed by sieving, thereby finally obtaining spherical bentonite cat litter with a particle size of 1-4 mm.
[0048] F. The performance index and application index of spherical soap clay cat litter were tested according to the method specified in T / CAQI 377-2024. As a result, the performance index and application index of spherical soap clay cat litter were as follows: moisture mass fraction (%) 7.4%, bulk density (g / cm 3 )0.82, deodorizing effect (ppm, in terms of NH3)12.0, formaldehyde not detected, lead (mg / kg)12.0, arsenic 1.5; water absorption rate (%)43, powdering rate (%)0.7, clumping strength (times, 30cm drop without breaking times)13.
[0049] Example 2
[0050] Except for using another natural bentonite ore to replace the natural bentonite ore in Example 1, spherical bentonite cat litter was prepared by using the same raw materials and process as in Example 1, and the same detection and analysis as in Example 1 was performed on the spherical bentonite cat litter.
[0051] As a result, the chemical composition of the obtained modified bentonite powder was: SiO2 53.10%, Al2O3 16.61%, TiO2 0.39%, iron oxide 5.90%, MgO 5.08%, CaO 3.31%, K2O 0.09%, and loss on ignition 15.13%.
[0052] As a result, the mineral composition of the obtained modified bentonite powder was: saponite 94%, montmorillonite 3.5%, and quartz 2.5%.
[0053] As a result, the fineness of the obtained modified bentonite powder was -200 mesh 93%.
[0054] As a result, the performance and application indicators of the spherical bentonite cat litter obtained are: moisture mass fraction (%) 7.4%, bulk density (g / cm 3 )0.82, deodorizing effect (ppm, in terms of NH3)12.0; water absorption rate (%)43, powderization rate (%)0.7, agglomeration strength (times, number of times of falling without breaking at 30cm)13.
[0055] Example 3
[0056] Except for using another natural bentonite ore to replace the natural bentonite ore in Example 1, spherical bentonite cat litter was prepared by using the same raw materials and process as in Example 1, and the same detection and analysis as in Example 1 was performed on the spherical bentonite cat litter.
[0057] As a result, the chemical composition of the obtained modified bentonite powder was: SiO2 52.71%, Al2O3 16.81%, TiO2 0.39%, iron oxide 5.92%, MgO 5.10%, CaO 3.46%, K2O 0.10%, and loss on ignition 15.11%.
[0058] As a result, the mineral composition of the obtained modified bentonite powder was: saponite 94.8%, montmorillonite 3.2%, and quartz 2.0%.
[0059] As a result, the fineness of the obtained modified bentonite powder was -200 mesh accounting for 93.2%.
[0060] As a result, the performance and application indicators of the spherical bentonite cat litter obtained are: moisture mass fraction (%) 7.5%, bulk density (g / cm 3)0.83, deodorizing effect (ppm, in terms of NH3)11.0, formaldehyde not detected, lead (mg / kg)11.0, arsenic 1.5; water absorption rate (%)43.3, powdering rate (%)0.71, clumping strength (times, 30cm drop without breaking times)13.
[0061] Example 4
[0062] Except that polyethylene glycol was used to replace the oleic acid amide in Example 1, spherical soap clay cat litter was prepared by the same raw materials and process as in Example 1, and the same detection and analysis as in Example 1 was performed on the spherical soap clay cat litter.
[0063] As a result, the chemical composition and mineralogical composition of the obtained modified bentonite powder were the same as those of Example 1.
[0064] As a result, the fineness of the obtained modified bentonite powder was -200 mesh accounting for 90.2%.
[0065] As a result, the performance and application indicators of the spherical bentonite cat litter obtained are: moisture mass fraction (%) 7.5%, bulk density (g / cm 3 )0.85, deodorizing effect (ppm, in terms of NH3)10.8; water absorption rate (%)42.8, powderization rate (%)0.83, agglomeration strength (times, number of times of falling without breaking at 30cm)12.
[0066] Example 5
[0067] Except that sodium dodecylbenzenesulfonate was used to replace the oleamide in Example 1, spherical bentonite cat litter was prepared by the same raw materials and process as in Example 1, and the same detection and analysis as in Example 1 was performed on the spherical bentonite cat litter.
[0068] As a result, the chemical composition and mineralogical composition of the obtained modified bentonite powder were the same as those of Example 1.
[0069] As a result, the fineness of the obtained modified bentonite powder was 89.4% in the range of -200 mesh.
[0070] As a result, the performance and application indicators of the spherical bentonite cat litter obtained are: moisture content (%) 7.3%, bulk density (g / cm 3 )0.88, deodorizing effect (ppm, in terms of NH3)10.2; water absorption rate (%)42.1, powderization rate (%)0.87, agglomeration strength (times, number of times of falling without breaking at 30cm)11.
[0071] Example 6
[0072] Except that the weight of oleamide was reduced from 1.2 kg in Example 1 to 0.5 kg, spherical bentonite cat litter was prepared using the same raw materials and process as in Example 1, and the same detection and analysis as in Example 1 was performed on the spherical bentonite cat litter.
[0073] As a result, the chemical composition and mineralogical composition of the obtained modified bentonite powder were the same as those of Example 1.
[0074] As a result, the fineness of the obtained modified bentonite powder was 88.4% in the range of -200 mesh.
[0075] As a result, the performance and application indicators of the spherical bentonite cat litter obtained are: moisture mass fraction (%) 7.55%, bulk density (g / cm 3 )0.86, deodorizing effect (ppm, in terms of NH3)10.7; water absorption rate (%)42.2, powderization rate (%)0.89, agglomeration strength (times, number of times of falling without breaking at 30cm)11.
[0076] Example 7
[0077] Except that the weight of oleamide was reduced from 1.2 kg in Example 1 to 3.0 kg, spherical bentonite cat litter was prepared using the same raw materials and process as in Example 1, and the same detection and analysis as in Example 1 was performed on the spherical bentonite cat litter.
[0078] As a result, the chemical composition and mineralogical composition of the obtained modified bentonite powder were the same as those of Example 1.
[0079] As a result, the fineness of the obtained modified bentonite powder was 88.3% in 200 mesh.
[0080] As a result, the performance and application indicators of the spherical bentonite cat litter obtained are: moisture mass fraction (%) 7.45%, bulk density (g / cm 3 )0.85, deodorizing effect (ppm, in terms of NH3)11.7; water absorption rate (%)42.8, powderization rate (%)0.79, agglomeration strength (times, number of times of falling without breaking at 30cm)12.
[0081] Example 8
[0082] Except that the aqueous solution containing 7% water glass was used instead of the aqueous solution containing 7% polyvinyl alcohol in Example 1 for granulation, spherical bentonite cat litter was prepared by the same raw materials and process as in Example 1, and the same detection and analysis as in Example 1 were performed on it.
[0083] As a result, the chemical composition and mineralogical composition of the obtained modified bentonite powder were the same as those of Example 1.
[0084] As a result, the fineness of the obtained modified bentonite powder was 88.2% in the range of -200 mesh.
[0085] As a result, the performance and application indicators of the spherical bentonite cat litter obtained are: moisture mass fraction (%) 7.39%, bulk density (g / cm 3 )0.89, deodorizing effect (ppm, in terms of NH3)11.5; water absorption rate (%)42.2, powderization rate (%)0.88, agglomeration strength (times, number of times of falling without breaking at 30cm)11.
[0086] Example 9
[0087] Except that the aqueous solution containing 7% acrylamide was used instead of the aqueous solution containing 7% polyvinyl alcohol in Example 1 for granulation, spherical bentonite cat litter was prepared by the same raw materials and process as in Example 1, and the same detection and analysis as in Example 1 were performed on it.
[0088] As a result, the chemical composition and mineralogical composition of the obtained modified bentonite powder were the same as those of Example 1.
[0089] As a result, the fineness of the obtained modified bentonite powder was 89.8% in the range of -200 mesh.
[0090] As a result, the performance and application indicators of the spherical bentonite cat litter obtained are: moisture mass fraction (%) 7.41%, bulk density (g / cm 3 )0.84, deodorizing effect (ppm, in terms of NH3)11.8; water absorption rate (%)42.6, powderization rate (%)0.85, agglomeration strength (times, number of times of falling without breaking at 30cm)11.
[0091] Example 10
[0092] Except that the drying temperature of the spherical soap clay cat litter was lowered from 260° C. in Example 1 to 230° C., the spherical soap clay cat litter was prepared using the same raw materials and process as in Example 1, and the same detection and analysis as in Example 1 was performed on the spherical soap clay cat litter.
[0093] As a result, the chemical composition and mineralogical composition of the obtained modified bentonite powder were the same as those of Example 1.
[0094] As a result, the fineness of the obtained modified bentonite powder was -200 mesh accounting for 93%.
[0095] As a result, the performance and application indicators of the spherical bentonite cat litter obtained are as follows: moisture content (%) 8.9%, bulk density (g / cm 3 )1.0, deodorizing effect (ppm, in terms of NH3)15.0; water absorption rate (%)42, powderization rate (%)0.9, agglomeration strength (times, number of times of not breaking after falling from 30cm)11.
[0096] Embodiment 11
[0097] Except that the drying temperature of the spherical soap clay cat litter was increased from 260° C. in Example 1 to 290° C., the spherical soap clay cat litter was prepared by using the same raw materials and process as in Example 1, and the same detection and analysis as in Example 1 were performed on the spherical soap clay cat litter.
[0098] As a result, the chemical composition and mineralogical composition of the obtained modified bentonite powder were the same as those of Example 1.
[0099] As a result, the fineness of the obtained modified bentonite powder was -200 mesh accounting for 93%.
[0100] As a result, the performance and application indicators of the spherical bentonite cat litter obtained are: moisture content (%) 6.6%, bulk density (g / cm 3 )0.77, deodorizing effect (ppm, in terms of NH3)17.0; water absorption rate (%)45, powderization rate (%)0.89, agglomeration strength (times, number of times of falling without breaking at 30cm)11.
[0101] Comparative Example 1
[0102] 100 kg of natural bentonite ore (the raw material is the same as that in Example 1) is randomly weighed from a large amount of natural bentonite ore and ground to obtain bentonite powder.
[0103] The fineness of the bentonite powder was obtained by sieving through a standard sieve. As a result, the fineness of the obtained bentonite powder was -200 mesh accounting for 93%.
[0104] The bentonite powder was granulated on a granulation disk with an aqueous solution containing 7% polyvinyl alcohol and sieved to obtain wet spherical bentonite particles of 1-4 mm.
[0105] The wet spherical bentonite particles were dried at 260° C. for 20 minutes, and fine particles with a particle size of less than 1 mm were removed by sieving, thereby finally obtaining spherical bentonite cat litter with a particle size of 1-4 mm.
[0106] The performance and application indicators of spherical bentonite cat litter were tested according to the method specified in T / CAQI 377-2024).
[0107] The results showed that the performance and application indicators of the spherical bentonite cat litter were as follows: moisture content (%) 8.0%, bulk density (g / cm 3 )1.10, deodorizing effect (ppm, in terms of NH3) 23.5; water absorption rate (%) 38, powderization rate (%) 1.3, agglomeration strength (times, number of times of falling without breaking at 30cm) 7.
[0108] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing spherical bentonite pet litter, characterized in that: The following steps are involved: The bentonite ore is mixed with a modifier and ground to obtain modified bentonite; The modified bentonite and the granulation auxiliary agent are mixed and granulated to obtain wet pet litter particles; Drying the wet pet litter particles to obtain spherical bentonite pet litter; The modifier is one or more of oleamide, polyethylene glycol or sodium dodecylbenzene sulfonate.
2. The preparation method according to claim 1, characterized in that: The weight ratio of the bentonite ore to the modifier is 100:0.5-5.
3. The preparation method according to claim 2, characterized in that: The grinding is dry grinding.
4. The preparation method according to claim 1, characterized in that: The mineral composition of the modified bentonite includes the following minerals in parts by weight: 90 to 100 parts of saponite, 1 to 5 parts of montmorillonite and 1 to 5 parts of quartz.
5. The preparation method according to claim 4, characterized in that: The chemical composition of the modified bentonite includes the following components: SiO2 52-54%, Al2O3 15-17%, TiO2 0.2-0.5%, iron oxide 3-6%, MgO 4-6%, CaO 2-5%, and K2O 0.05-0.15%.
6. The preparation method according to claim 5, characterized in that: The ignition loss of the modified bentonite is 10-20%.
7. The preparation method according to claim 1, characterized in that: The granulation auxiliary agent is one or more of water glass solution, polyvinyl alcohol aqueous solution or acrylamide aqueous solution.
8. The preparation method according to claim 7, characterized in that: The volume percentage concentration of the polyvinyl alcohol aqueous solution is 5-10%; And / or, the volume percentage concentration of the water glass solution is 5-10%; And / or, the volume percentage concentration of the acrylamide aqueous solution is 5-10%.
9. The preparation method according to any one of claims 1 to 8, characterized in that: The drying temperature is 200-300°C; The drying time is 10 to 30 minutes; And / or, the particle size of the spherical bentonite pet litter is 1 to 4 mm.
10. Spherical bentonite pet litter prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Bentonite cat litter and preparation method thereof
CN107897009A
Preparing method of hydrous aluminosilicate clay cat litter
CN106431453A
Environmental-friendly attapulgite clay-based cat litter and preparation method therefor
CN111316924A
Preparation process of puffed cereal cat litter
CN115152643A
Granular treating material for animal excrement
JP2000060338A